Legal Protection of Indigenous Peoples Under International Environmental Law - Marah, Thomas Sheku (Indonesian Journal Publisher, 2025)
Indigenous peoples have a unique relationship with their environment, but they are under immense threat from environmental destruction, dispossession of land, and climate change. Even with the UNDRIP and CBD, although there are frameworks comprehensively defining their rights, protective measures lack adequate enforcement and are superficial at best. This article intends to focus on how much international environmental law extends in protecting an indigenous person's environmental rights by conducting a normative legal analysis of basic international treaties, case law, and regional human rights adjudications. The results suggest a gap between extensive legal recognition of indigenous rights and the perpetual challenge of state-controlled borders, corporate dominance, and insufficient enforcement policies. There are major gaps regarding the violation of FPIC, legal and illegal land tenure thresholds, widespread poverty, and restricted civil participation in the Amazon, Southeast Asia, and East African regions. The article examines gaps such as minimal legal oversight and looser regulation on state and corporate actors that impede shielded privileges from public scrutiny. To achieve these objectives, the author suggests strengthening these identified gaps through the establishment of bottom-up accountability approaches, integration of indigenous law frameworks, and an approach that views governance and environmental issues as human rights matters. The study advocates for the incorporation of indigenous peoples as active participants at the national and international levels of environmental governance, with full legal recognition and protection of their rights.